Rabindra Sangit (songs of Rabindranath Tagore): a Bibliometric Study - Ray, Partha Pratim; Sen, B. K. (Journal of Information and Knowledge, 2013)
Rabindranath Tagore has composed more than two thousand songs. His songs known as Rabindra Sangit have become a symbol of cultural ethos of both India and Bangladesh. The present paper is an attempt to study the growth of Rabindra Sangit, Tagore’s writings on songs as well as its publication trends with the help of bibliometric technique. It is observed from the study that songs and writings on songs in different literary forms constitute a substantial part of Tagoreana (all the intellectual output of Rabindranath). Tagore composed songs throughout the different phases of his literary career.